Indonesia Grapples with the Indo-Pacific: Outreach, Strategic Discourse, and Diplomacy. Issue 2 (August 2019) - Scott, David
This article analyses and evaluates Indonesia's grappling with the Indo-Pacific. Analysis is threefold – Indonesia's actorness in the Indo-Pacific, its strategic discourse on the Indo-Pacific, and its Indo-Pacific diplomacy. Actorness is pursued with regard to Indonesia's more active involvement in regional and subregional structures in the Indian Ocean and Pacific Ocean. Strategic discourse is threefold – Natalegawa's "Indo-Pacific Treaty" concept (2013–2014), Widodo's "maritime nexus" drive (2014 onwards), and the current "Indo-Pacific Cooperation Concept" (IPCC; 2018 onwards). Diplomacy is pursued with regard to Indonesia's relationship with Australia, Japan, China, India, and the United States. The article concludes that while Indonesia certainly is on the rise as an Indo-Pacific actor, its continuing naval weakness undermines Indonesia's "maritime nexus" stance, while its reluctance to challenge China leaves Indonesia's Indo-Pacific Treaty and its IPCC vague and to some degree ignoring uncomfortable security issues posed by China. A closer synergy for Indonesia with the US and Japanese Free and Open Indo-Pacific initiative is suggested.